SC41 A five week apprenticeship programme for final year medical students culminating in a simulated on-call shift. (November 2018) - Rizkalla, Amanda; Patel, Jason; Salam, Omolola; Taylor, Russell; Elshafie, Sally; Kerks, Jennifer
Abstract : Background: Multiple studies have shown a perceived lack of preparedness of final year medical students transitioning to doctors. Skills required on-call such as prioritisation, prescribing and acute clinical management have been reported as the areas in which they felt least prepared. 1 A simulated on-call day, 'bleep day', had already been piloted at New Cross Hospital and had good feedback from University of Birmingham final year medical students. However, the bleeps were spread throughout the day so there was no element of time pressure or prioritisation. The students also reported feeling unprepared as there was no specific teaching around the tasks demanded of them on the day. Summary of work: We formulated a five week 'apprenticeship programme' of tutorials based on the themes of prescribing, 'you've been bleeped, ' data interpretation and miscellaneous tasks to aid preparation for the final 'bleep day'. These apprenticeship tutorials were designed based on the authors' experiences of difficult scenarios faced as a new FY1 doctor when on-call covering the wards. The final 'bleep day' simulation took place at the end of these five weeks. Students were bleeped to various low fidelity simulation stations over three hours based on the themes covered during the 'apprenticeship' programme. During this time they were expected to prioritise and manage tasks within their limits of competence and escalate concerns to a senior as deemed appropriate. Summary of results: (see table 1) Discussion and conclusions: This experience provided the students with the opportunity to practice technical and non-technical clinical skills in a safe environment. Feedback from the students showed improved perceived preparedness for on-call ward cover shifts. We feel this is due to the apprenticeship programme and the realism of a time pressured simulated on-call shift. We hope this will reduce anxiety, enhance clinical performance and help promote patient safety in the early stages of these students' careers. Recommendations: In the future we aim to survey how the students feel the programme impacted on their experiences in their first month of working with a view to expanding the programme to other trusts within the region.